Pre-exposure prophylaxis for HIV prevention in women: current perspectives - Flash, Charlene A (Int J Womens Health, 2017)
There are ~900,000 new HIV infections among women every year, representing nearly half of all new HIV infections globally. In the US, nearly one-fifth of all new HIV infections occur among women, and women from racial and ethnic minority communities experience disproportionately high rates of new HIV infections. Thus, there is a need to develop and implement effective HIV prevention strategies for women in the US and internationally, with a specific need to advance strategies in minority communities. Previous studies have demonstrated that oral HIV pre-exposure prophylaxis (PrEP), the use of antiretroviral medications by HIV-uninfected persons to prevent HIV acquisition, can reduce HIV incidence among women who are adherent to PrEP. However, to date, awareness and uptake of PrEP among women have been very limited, suggesting a need for innovative strategies to increase the knowledge of and access to PrEP among women in diverse settings. This narrative review summarizes the efficacy and safety data of PrEP in women, discusses considerations related to medication adherence for women who use PrEP, and highlights behavioral, social, and structural barriers to maximize the effectiveness of PrEP in women. It also reviews novel modalities for PrEP in women which are being developed and tested, including topical formulations and long-acting injectable agents that may offer advantages as compared to oral PrEP and proposes a community-oriented, social networking framework to increase awareness of PrEP among women. If women are provided with access to PrEP and support to overcome social and structural barriers to adhere to PrEP, this prevention strategy holds great promise to impact the HIV epidemic among women in the US and globally.